What's new in the pathogenesis of the coagulopathy in acute promyelocytic leukemia?. Issue 2 (March 2016) - Mantha, Simon; Tallman, Martin S.; Soff, Gerald A.
Abstract : Purpose of review: Acute promyelocytic leukemia (APL) is associated with a complex coagulopathy. In spite of substantial recent improvements in treatment regimens, hemorrhagic death remains the main cause of induction failure. In this review, we delineate recent understanding of the pathophysiology and management of the hemorrhagic diathesis of APL. Recent findings: Laboratory and clinical data suggest that the malignant leukocytes mediate the hemorrhagic diathesis associated with APL through multiple mechanisms which lead to a combination of consumptive coagulopathy and primary hyperfibrinolysis. Exposure of tissue factor and Annexin II by the leukemic blasts is the main determinants of these processes. Promyelocyte-derived microparticles have recently been implicated in the coagulopathy as well. Total white cell count and platelet count have emerged as good general predictors of hemorrhagic death, along with the different routine hemostatic parameters. Prompt treatment with all-trans retinoic acid, with or without arsenic trioxide, is the most important step in preventing bleeding complications. Repletion of coagulation factors and platelets with blood products remains the mainstay of supportive treatment, whereas the role of recombinant soluble thrombomodulin is currently being investigated. Summary: The coagulopathy of APL is multifactorial, with both disseminated intravascular coagulation and primary hyperfibrinolysis mediated largely by the malignant leukocytes.